Comunicação e divulgação científica de líderes de grupos de pesquisa no campo CTS: análise a partir de indicadores bibliométricos e altmétricos - Galdino, Rejane (2020)
Science has consolidated itself in the social structure as much as technology, both differing in the relationship established with society. The scientist has as a commitment to science the need for scientific communication and its social function is scientific dissemination. Taking into account the proximity between the STS field and the scientific communication and dissemination processes, this research aims to investigate the scientific publication and dissemination practices of leaders of research groups in the STS field, registered with CNPq. This is an exploratory and descriptive research that aims to verify whether researchers working in the STS Field comply with the science dissemination assumptions recommended by the Field itself. With regard to the characterization of the STS groups and the scientific production of the leaders, the area of Education has great prominence in STS studies, proposing, predominantly, to study the ways in which the STS field impacts education and the way in which Education can contribute to advances in the STS field, such as deepening and discussing ways of dealing with the issue of scientific illiteracy, which is among the themes of greatest study by leaders. Bibliometric and altmetric indicators pointed out that bibliographic production and more traditional channels, such as congresses and journals, are the most used by leaders for scientific communication. In the altmetric analysis of the articles published by the leaders, Mendeley, the academic social network, received the most attention online. Of the 87 leaders of STS research groups, 17 are authors of articles that received attention online. It is concluded that although leaders denote having a consolidated scientific communication, according to the methods used in this research, they show that there is still a way to go for effective engagement in scientific dissemination through social networks, which in a way denotes that the premises advocated by the STS Field itself of the greatest proximity between researchers and society should be encouraged.